Ocorrência de miopatias emergentes e a qualidade e estabilidade oxidativa de peitos de frango estriado (White Striping) - Carvalho, Leila Moreira de (2020)
The worldwide increase in the demand and consumption of chicken meat over the last decades has caused a pressure in the production systems which have tried to optimize chicken meat production. To fulfil the objective, an intense genetic selection and the improvement of animal feeding programs has led to animals with greater weight gain in a reduced period, associated with a lower cost. As a consequence of this biological pressure to grow fast, new myopathies have appeared, among them, White striping (WS) and Wooden breast (WB). The aim of this study was to analyze the occurrence of WS and WB myopathies in Northeastern Brazil, to evaluate the use of near infrared spectroscopy (NIRS) to classify breasts affected by these myopathies in an industrial slaughter plant, to investigate the effect of WS myopathy on meat quality, focusing on understanding the molecular mechanisms behind oxidative stress, and to assess how acceptability, purchase intent and emotions evoked in consumers has been affected by awareness of the causes of WS myopathy. In a first study, the occurrence of WS and WB breasts (isolated and/or combined) in birds of different age ranges (4-5, 6-7, 8-9 and 65 weeks) was verified in a commercial plant using traditional method of detection (palpation and visual aspect of the muscle). The use of near infrared spectroscopy (NIRS) associated with the SPA-LDA and SIMCA classification models was also tested as a tool to distinguish Normal (N), WS, WB and WS/WB breasts. In a second study, WS chicken breasts, with moderate and severe degrees of myopathy, were analyzed for physical-chemical properties, quality characteristics, endogenous antioxidant defenses, oxidative damage to the lipid and protein fraction, and discrimination of sarcoplasmic proteins using a Q Exactive Orbitrap mass spectrometer. In a third study, the attitude of Spanish consumers was evaluated regarding the awareness of the WS myopathy causes and consequences, and how the recognition of these breasts influences the acceptability, purchase intention and emotions evoked by consumers. The results demonstrated a high occurrence of myopathies WS, WB and WS WB in Brazil, and seem more frequent and present themselves in a more aggravated form in birds of older slaughter age. In addition, meats with myopathies presented a compromised nutritional value. The NIRS technique associated with the SPA-LDA classification model presented high accuracy in the identification of Normal (without myopathies), WS and WB (isolated and combined with WS) meats, regardless of the birds’ slaughter age. Meats affected by WS showed greater depletion of free thiols, and more intense formation of malonaldehyde, allysine and Schiff base; in addition to impaired activity of endogenous antioxidant enzymes catalase, superoxide dismutase and glutathione peroxidase. The proteomic study revealed a failed attempt to maintain the biological function of muscle fiber and redox homeostasis. Striated chicken breasts (WS) showed low acceptability and purchase intent, especially when consumers were provided with information about the causes and consequences of this myopathy. The meat cooking process was able to mask the visualization of white streaks, leading consumers to have a preference for WS meat over Normal meat in unreported conditions of consumption; whereas under informed conditions, 20% of consumers tended to reject the consumption of WS meat. Furthermore, the emotional profile of consumers was significantly affected by the awareness of WS myopathies, as consumers felt more "interested" and "enthusiastic" and less "good-natured", "loving" and "warm" when consuming these meats. Based on the results generated in this research it was possible to conclude that the level of occurrence and the degree of myopathies in the breast muscle is directly related to the age of slaughter of the birds. It was also possible to confirm the promising use of the NIRS technique in the identification of myopathies in industrial processing lines. Furthermore, it showed that WS breasts present highest susceptibility to oxidative stress and, consequently, impairment of physiological and metabolic processes of the muscles. In addition, it showed that the benefit of information on what consumers eat compromise the acceptability, purchase intent and emotions evoked during consumption of striated chicken breasts.